Leucoagaricus purpurascens, a new species from eastern China based on morphological characteristics and molecular evidence - Guo, Ting; Ma, Yun-Rui; Yang, Rui-Heng; Ge, Zai-Wei; Bao, Da-Peng (Phytotaxa, 2023)
A new species, Leucoagaricus purpurascens, collected from a subtropical region in China, is described based on morphological and molecular data. Leucoagaricus purpurascens is characterized by its small basidiomata with purple discolouration when dried, the pileus with distinct umbo, the amygdaliform, ellipsoidal to oblong basidiospores, and the absence of cheilocystidia. A detailed morphological description, line drawings, colour photographs, and a phylogenetic tree showing the phylogenetic placement of the new species are provided.